Influence of Dynamically Stable‐Unstable Flow on Seawater Intrusion and Submarine Groundwater Discharge Over Tidal and Seasonal Cycles. Issue 4 (23rd April 2022) - Fang, Yunhai; Zheng, Tianyuan; Wang, Huan; Zheng, Xilai; Walther, Marc
Abstract: Temporal changes in the external forcing conditions of coastal aquifer systems, such as seasonal inland freshwater input, may disturb the balance between the ocean forces and freshwater hydraulic gradient. An increase or decrease in this imbalance may affect the stability of tide‐induced upper saline plume (USP). In this study, we performed laboratory experiments and numerical simulations to investigate the influence of seasonal inland freshwater input on USP stability and the associated behavior of seawater intrusion (SWI) and submarine groundwater discharge (SGD). In contrast to previous studies, we found that USP was not always stable or unstable in the intertidal zone, but experienced a dynamically stable‐unstable process as the seasonal inland freshwater input varied. The extent of SWI and SGD showed a dual response to the seasonal inland freshwater input. On one hand, seasonal fluctuation in inland freshwater input directly induced responsive changes in SWI and SGD; on the other hand, dynamic stability of the USP caused by the seasonal fluctuation resulted in an additional high‐frequency fluctuation in the extent of SWI and SGD during the unstable flow. Moreover, the response of saline SGD and total SGD to the seasonal fluctuation in the inland freshwater input was nonlinear. This overall increased the SGD compared to the scenarios with a temporally constant inland freshwater input. Therefore, ignoring seasonal changes in the inland freshwater input may underestimate the amount of water exchanges across the aquifer‐sea interface. Plain Language Summary: Submarine groundwater discharge (SGD) represents the water flux across the land‐ocean boundary into the ocean. SGD has been increasingly recognized as a key route of delivering land‐based fresh water, metals, nutrients, and carbon into the ocean, which affects coastal water quality and ecosystems. Extensive studies have shown that SGD changes in time and space and is controlled by various influence factors. Among others, seasonal changes in fresh groundwater recharge and gravity‐driven flow caused by a dense salt water upon a less dense fresh water are two critical factors. However, the combined effects of these factors and their individual contributions remain unclear. In this study, we used physical and numerical methods to investigate the response of SGD under the combined effects of these factors. The results showed that SGD was affected by both fresh groundwater recharge and gravity‐driven flow, with a greater influence of fresh groundwater recharge. In addition, seasonal changes in fresh groundwater recharge resulted in an increase in the flux of SGD. These findings provide a new understanding of the complex water cycle between ocean and land. Key Points: Dynamically stable‐unstable flow occurs in the intertidal zone with varying seasonal inland freshwater input The extent of seawater intrusion and submarine groundwater discharge (SGD) show a dual response to seasonal inland freshwater input Neglecting the seasonal fluctuation in the inland freshwater input may underestimate the amount of SGD